Recent Trends in Asian ESP - Amporn Sa-ngiamwibool (International Conference on Education and Language (ICEL), 2014)
Due to internationalization and growth of business, English for specific needs has become increasingly important worldwide. English Specific Purposes (ESP) playsa more vital role in Asia. A review of recent trends in ESP revealed the growth of ESP practice in Asian contexts.  This study therefore explored recent trends in Asian ESP from 2011 to 2013.  The Asian ESP Journal as a flagship journal was chosen for a content analysis in this study. Descriptive statistics was used for data analysis to draw the conclusion of the study.  Results of the study revealed trends infour areas of interest: authors and geographical origins of articles, topics, skills and targets. Several Asian trends and possibilities were highlighted. Further inquiry should examine a specific area of interest.